Conceptualising public-private partnerships for social innovation through community engagement in higher education institutions - Sibhensana, B.; Maistry, S. (South African Journal of Higher Education, 2023)
The achievement of human social and economic development has been equated to social innovation. Innovation that focuses on the marginalised communities in South Africa becomes necessary to redress the inequalities created pre-democracy. As social institutions, higher education institutions are well positioned to deal with the challenges of the 21st century, which include poverty, unemployment and inequality, through promoting social innovation. In democratic South Africa the relationship between an institution of higher learning and the community can be viewed as a social innovation. This submission implies that one of the objectives of community engagement as a core function of universities, is to drive the social innovation agenda. The university’s contributions to community development can be viewed in terms of its ability to commit to social innovation. It is a better vehicle for understanding and creating social value in all its forms. Social innovations thrive on collaborative action involving public, private, civic organisations and the community. Community engagement provides an opportunity for higher education to address communities’ socio-economic challenges through forming partnerships that are mutually beneficial to all parties involved. Active participation of universities, communities and grassroots organisations ensures that the innovations produce social outcomes that genuinely address the needs of the communities. Higher education institutions can promote the formation of diverse cross sectoral partnerships involving communities and community-based organisations in promoting social innovation, which is a crucial driver for community development. Developing mutual trusting relationships creates a conducive environment to foster social innovations. This conceptual article will discuss how universities can promote the formation of public-private partnerships for social innovation through community engagement. Rhodes university’s community engagement division is used as a case study to inform the discussions. The practice of community engagement at Rhodes university community engagement division thrives on the formation of collaborative and mutually beneficial community-university partnerships that promote socially innovative strategies in addressing community challenges.